A prospective study of clinical profile, management and outcome of surgical treatment of perforated peptic ulcer in northern India: a tertiary hospital experience - Mahesh Kuldeep; Bhanwar Lal Barkesiya; Dinesh Barolia; Pooja Kuldeep (International Journal of Medical Research and Review, 2015)
Introduction: This is a prospective study of patients of adult age group admitted with clinical features suggestive of perforated peptic ulcer. The study comprised of 70 patients. In our study we aimed to provide a complete epidemiological, clinical and management description of Peptic ulcer Perforation in adult age group patients.Methods: all the patients who were undergoing exploratory laparotomy were taken. A detailed history, thorough clinical examination and necessary routine blood investigations and X-ray chest and flat plate abdomen in standing position were performed in each case.Results: Perforated peptic ulcer is more common in male in the age group 30-50 years and most common presenting symptom was pain abdomen. Smoking and alcohol beverage consumption were risk factors in most cases (78.5%) in causation of perforation. Most common site of ulcer perforation is duodenal 1st part (94.3%). Out of 63 patients in whom perforation size was <=1cm, 10 (15%) were in shock. Whereas 2 were in shock out of 7 patients with perforation size >1 cm. Size of perforation is directly proportional to the quantity of peritoneal fluid.Conclusion: Peptic ulcer perforation in present scenario is a disease of relatively younger age group. Rural background, poor socioeconomic status and occupation like farmer and labourer seem to contribute to causation of peptic ulcer perforation. The most important risk factors for the determination of mortality in perforated peptic ulcer disease are duration of perforation (especially if >24 hrs), condition of the patient at the time of presentation, size of perforation as well as preoperative management.